PENGARUH PROFITABILITAS, UKURAN PERUSAHAAN, KEPEMILIKAN PUBLIK DAN KOMITE MANAJEMEN RISIKO TERHADAP PENGUNGKAPAN MANAJEMEN RISIKO - Nur Annisa Ariyanti; Asri Dwi Ariyani; Marsuking; Kusumaningdiah Retno Setiorini (JAE (JURNAL AKUNTANSI DAN EKONOMI), 2026)
This study aims to analyze the effect of Profitability, Company Size, Public Ownership and Risk Management Committee on Risk Management Disclosure. This study is a quantitative study using secondary data on the financial statements of companies in the banking sector listed on the Indonesia Stock Exchange for the period 2021-2023. The sample in this study was 40 companies with a purposive sampling technique. The data analysis method uses multiple linear regression. Analysis of the research results using SPSS 30. The results of the study indicate that simultaneously Profitability, Company Size, Public Ownership and Risk Management Committee have an effect on Risk Management Disclosure, Profitability partially does not have an effect on Risk Management Disclosure, Company Size partially has an effect on Risk Management Disclosure, Public Ownership partially has an effect on Risk Management Disclosure, Risk Management Committee partially has no effect on Risk Management Disclosure.